(untitled) (Research, Society and Development, 2021)
Objective: To characterize the self-care practices of adults with Type 2 Diabetes Mellitus (DM type 2) and to describe the role of the nursing staff during the care of these patients in different health care centers in Tegucigalpa, Honduras. Methodology: Quantitative, descriptive, cross-sectional approach, with a sample of 73 adults of both sexes, selected non-probabilistically by convenience. Data collection was carried out with the electronic instrument "Google Forms", in May 2020, using descriptive statistics for data analysis. Results: these were presented in the form of descriptions, graphs, and tables. Concerning the sociodemographic characteristics: the predominance of the female sex was observed with 59%. The 30.6% reported receiving less than the Honduran minimum wage (Lps. 8000.00 -10,000.00). Regarding medication: Metformin was confirmed to be the most used medication (46.6%). Among the self-care measures, it was found that: most adults with type 2 DM perform daily blood glucose level controls; engage in physical activity and eat a balanced diet; check their feet daily and consider taking the treatment correctly. In addition, 94.5% reported receiving education on self-care by the nursing staff every time they go to the hospital. Conclusion: most of the adults with type 2 DM studied reported performing self-care actions. However, there are gaps in knowledge about the disease and the correct use of medications. Therefore, the role of nursing in the health education of this population is of vital importance.